HUBUNGAN KOMPONEN PERILAKU (PENGETAHUAN, SIKAP, TINDAKAN) MEROKOK PADA MAHASISWA PSIK UNITRI ANGKATAN 2009 - Wenfridus R.R Lake; Sugianto Hadi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2014)
Behavior is an individual's reaction to stimuli that are very influential to the person both inside and outside his/her personal. To avoid negative behavior, such as smoking especially students need early treatment and a positive pressure so that we hope can be achieved. The purpose of this study is to identify the relationship between knowledge, attitudes and actions of smoking on students of Nursing Science Program University of Tribhuwana Tunggadewi Malang Year 2009. Research design use correlational with Cross Sectional method. Total population 48 people with 43 samples taken with purrpusive sampling. Instrument that uses a questionnaire with nominal, ordinal scale, and be analyzed use Spearman's rho test. The result of the study showed most students 72.1% had a good knowledge. While for positive attitude there is 90.7% and action showed 44.2%. The result of analysis show p value 0.000 (